Corportae Governance Issues in Nepalese Banks and Financial Insti-tutions and Legal Settelement at the Supreme Court of Nepal - Vaidya, Rashesh; Pradhan, Prajan; Patel, Sunil Kumar (Khwopa Journal, 2023)
Corporate governance includes a set of relationships among Board of Directors, management team, employees, and other stakeholders of an organization. Corporate governance is a mechanism that determines the setting of goals, attainment of objectives, and monitoring of the performance of an entity. Banks and financial institutions (BFIs.) in Nepal have been under great concern regarding good corporate governance from the regulatory body, Nepal Rastra Bank (NRB), a central bank of Nepal. After back-to-back off-site supervision and on-site supervision, issues of corporate governance have come to the surface. Issues of corporate governance at Nepalese BFIs go beyond the picture reflected in the books of accounts and financial indicators. Hence, issues of corporate governance have been raised in the courtrooms of Nepal. Thus, the paper conducted a case study on the issues of corporate governance within Nepalese BFIs. In such a scenario, the Supreme Court of Nepal, in most cases, gave verdicts in favor of the central bank, found the top managerial personnel to be the main culprit, and ordered it to settle the issues as corporate governance comes under the jurisdiction of NRB.